Total and added sugar intakes, sugar types and cancer risk: results from the NutriNet-Santé cohort. (30th September 2020) - Debras, C; Chazelas, E; Srour, B; Kesse-Guyot, E; Julia, C; Galan, P; Hercberg, S; Latino-Martel, P; Deschasaux, M; Touvier, M
Abstract: Background: Excessive sugar is now recognized as a key risk factor for several cardiometabolic diseases. In contrast, the associations between sugars and cancer risk in cohort studies have been less investigated, and data is lacking regarding differential effect of sugar types and sources. Experimental data suggest that sugars could play a role in cancer etiology, through obesity but also through inflammatory and oxidative mechanisms and insulin resistance. Our objective was to study the associations between total and added sugar intake and cancer risk, accounting for sugar types and sources. Methods: 101, 279 French adults from the NutriNet-Santé prospective cohort study (2009-2019) were included. Sugar intake was assessed using repeated 24h-dietary records, designed to register participants' usual consumption for more than 3, 500 food and beverage items. Associations with cancer risk were assessed by multi-adjusted Cox proportional hazard models. Results: Sugar intake was associated with increased cancer risk (2, 503 cases, Hazard Ratio Quartile 4 vs 1=1.17, 95% Confidence Interval 1.00-2.37, P trend=0.02). This association was mainly driven by breast cancer (783 cases, HR Q4 vs Q1=1.51 (1.14-2.00); P trend=0.0007) and remained significant even when weight-gain during follow-up was accounted for. Associations were more specifically observed for added sugars (P trend=0.02), free sugars (P trend=0.007), sucrose (P trend=0.01), and sugars from milk-based desserts (P trend=0.02), from sugary drinks (P trend=0.002), and from dairy products (P trend=0.01). Conclusions: These results suggest that sugar (especially added sugar), of which intake is increasing in Western countries, may represent a modifiable risk factor for cancer prevention, adding to its well-established effect on dental and cardiometabolic health. These findings provide important and novel insights to the current debate on the implementation of sugar taxation, marketing regulation, and other sugar-related policies. Key messages: In this large-scale prospective cohort of French adults, sugar intake (especially added sugar) was associated with higher cancer risk. These results suggest that (added) sugar may represent a modifiable risk factor for cancer prevention, adding novel insights to current debates on implementing sugar-related public health policies.